Kingdom of the Netherlands : Netherlands Antilles; 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of the Netherlands; Netherlands Antilles. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The 2008 Article IV Consultation analyzes the promise of fiscal discipline and debt relief that has boosted investor confidence and growth in the Kingdom of the Netherlands-Netherlands Antilles. Although exports moderated temporarily, tourism was a bright spot owing to improvements in competitiveness as a result of infrastructure investments, and cost controls from immigration. Executive Directors encouraged the authorities to take the opportunity provided by the large debt relief from the Netherlands government under the dissolution agreement to set the budget and the economy on a more sustainable footing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet